The Cooperative Learning and its impact on the Teaching Learning Process of the English Language with the students of 8th, 9th, and 10th years of Basic Education at “Nuestra Señora del Rosario Technological Institute”. Academic year 2010 to 2011 - Figueroa Cabrera, Johanna Verónica (2011)
The present research work titled “The Cooperative Learning and its impact in the Teaching Learning Process of English Language with the students of 8th, 9th and 10th Years of Basic Education at “Nuestra Señora Del Rosario” Technological Institute, Academic Year 2010 – 2011”, its general objective is to determine if the Cooperative Learning impacts in the Teaching Learning Process of the English Language with the students of 8th, 9th, and 10th years of Basic Education at “Nuestra Señora del Rosario Technological Institute”. Academic year 2010 to 2011. In this investigation, the scientific method was used through a logical and systematic procedure to discover the truthfulness of the facts. The inductive and deductive methods were employed to study, to analyze and to extract the respective conclusions about the topic. The analytic – synthetic method served to analyze the empiric information after applying the instruments. The descriptive method was useful to elaborate the description of the problem, to draw up the objectives, to define the theoretical frame, to determine the hypotheses and to select the techniques which permitted the collection and interpretation of the information in a coherent way. To make possible the collection and organization, processing, analysis of the data a survey applied to teachers and students. The main results that we can found is that Cooperative Learning elements are not applied by teachers and the Techniques of Cooperative Learning applied by teachers are not getting good results in Teaching Learning Process of English Language and teachers develop their classes in a traditional way, which limits students' learning.